The Effect of Facilities and Infrastructure on Students’ Interest in Visiting the Library at SMA Muhammadiyah 2 Palembang - Ramadhan, Gilang; Zulkipli; Ade Akhmad Saputra (The Future of Education Journal, 2026)
This study aims to analyze the effect of library facilities and infrastructure on students’ interest in visiting the library at SMA Muhammadiyah 2 Palembang and to determine whether such an effect exists. This research employed a quantitative approach. The sampling technique used was simple random sampling, in which samples were selected randomly from the population without considering strata. The population consisted of 589 students, and the sample size was determined as 10% of the population, resulting in 86 respondents. The library facilities and infrastructure variables in this study were based on the National Library Standards (SNP) No. 12 of 2017. Data analysis was conducted using simple linear regression with SPSS version 23. The results of the study partially indicate that the facilities and infrastructure variable (X) has a significant effect on students’ interest in visiting the library at SMA Muhammadiyah 2 Palembang. This is evidenced by the t-value (20.113) being greater than the t-table value (1.98525) and the significance value (0.000) being less than 0.05. Thus, it can be concluded that library facilities and infrastructure significantly influence students’ interest in visiting the library.